Playful Philosophy and Serious Sophistry : a Reading of Plato's ""Euthydemus"" - Sermamoglou-Soulmaidi, Georgia (Untersuchungen zur antiken Literatur und Geschichte., 2014)
This book provides an interpretation of Plato's Euthydemus as a unified piece of literature, taking into account both its dramatic and its philosophical aspects. It sheds new light on some old questions, including the relation between knowledge, virtue and happiness. Further, it pays due attention to the arguments of the sophists that are often neglected, focusing on the similarities between Socrates and his eristic opponents.